Archi-text-ture: Architecting Through Writing - Johannes Adiyanto (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
Architecture is often understood as a real and tangible science, in the form of space and form. This understanding is associated with the origin of the word ‘techne’ which refers to the engineering in the construction process of a building, an architectural work. Writing on new architecture developed around 1968, at a time when architectural criticism by Louis Huxtable became known although the form of writing, identification both in pictures and description, had been done since the time of the Roman Empire by Vitruvius and later interpreted by Leon Battista in the Renaissance. This paper describes descriptively several examples and categories of writing about architecture, especially in Indonesia. The study uses an exploratory study approach with reference to the theory of architectural criticism from Attoe’s understanding. The descriptive exploration of this paper shows there are at least four categories of architectural writing in Indonesia, from those aimed at creating architectural narratives to making architectural texts which are then called archi-text-ture in the paper. The paper is not a final paper, because it is the start of a long textual journey, so it is made as an archi-text-ture construction process and to open up opportunities for further interpretation and development